Does Covid 19 Pandemic Have a Direct Impact on the Level of Trust and Commitment toward Hospitals as Health Service Providers in Yogyakarta? - Yuni Heriyanti (Ilomata International Journal of Social Science, 2021)
The purpose of this study was to examine the direct and indirect effects of the pandemic on consumer trust and consumer commitment towards public health care in Yogyakarta during the pandemic. The research method in this study was the survey method with path analysis tools. Based on the research result it can be concluded that the direct impact of the Covid pandemic (X) on trust (Y1) is 0.205 (unstandardized) and 0.187 (standardized), the direct impact of trust (Y1) on the Y2 commitment is 0.602 (unstandardized) and 0.63 (standardized). Based on the t-test on the Sobel formula, the t value (3.251) > t table (1.663), means that there is an indirect impact between variable X (pandemic) on Y2 (commitment) through Y1 (trust). The impact of the Covid pandemic indirectly affects consumer commitment through the variable of trust with a combined direct and indirect impact of 1,099.